Reliability-based safety factor for metallic strip flexible pipe subjected to external pressure. (15th January 2018) - Liu, Ting; Leira, Bernt J.; Fu, Ping; Bai, Yong; Liu, Dahui
Abstract: Reliability-based safety factors for metallic strip flexible pipes(MSFP) subjected to external pressure are calibrated in this paper. The partial safety factors of such pipes are obtained by introducing a target reliability index and using a combination of Monte-Carlo simulation and FORM. The relationship between the safety factors and the coefficient of variation for key basic variables as well as the impact of different distribution types for both the resistance and load effect parameters on the calibrated results are investigated. Recommended design safety factor for MSFP is given similar to the widely used design safety factor for conventional metallic pipes. The calibration process presented in this paper is relatively easy to understand and to carry out. This also applies to cases with multiple components and even requiring complex iterations in relation to the mechanical model. The results obtained here can provide some guidance in connection with manufacturing procedures at the initial design stage of the MSFP. Highlights: A calibration process of the reliability-based safety factor which is easy to understand and to carry out is presented. Reliability-based safety factor for metallic strip flexible pipes(MSFP) subjected to external pressure is calibrated. Recommended design safety factor for MSFP is given in this paper. The impact of different distribution types for the resistance and load effect on the calibrated results are studied.